THE INFLUENCE OF HEDONIC VALUE AND UTILITARIAN VALUE ON BRAND TRUST AND LOYALTY - Achmad, Gusti Noorlitaria; Hudayah, Syarifah; Ilmi, Zainal (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to examine and analyze the influence of Hedonic Value and Utilitarian Value on Brand Trust and loyalty on shoe products. This research will be conducted by distributing questionnaires to 100 respondents who use shoe products. The analysis technique used is quantitative analysis techniques with path analysis methods. The results of this study indicate that the hedonic value has a significant positive effect on brand trust. Utilitarian values do not have a significant influence on brand trust. Brand trust has a significant positive effect on Loyalty.